2007
DOI: 10.1111/j.1469-8137.2007.02289.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibited polar auxin transport results in aberrant embryo development in Norway spruce

Abstract: Summary• Current hypotheses concerning the role of polar auxin transport in embryo development are entirely based on studies of angiosperms, while little is known about how auxin regulates pattern formation in gymnosperms.• In this study, different developmental stages of somatic embryos of Norway spruce (Picea abies) were treated with the polar auxin transport inhibitor 1-Nnaphtylphthalamic acid (NPA). Effects of the treatments on auxin content, embryo differentiation and programmed cell death (PCD) were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 32 publications
0
70
0
Order By: Relevance
“…A recent study by us, 2 along with a study by Larsson et al 24 have shown that growth of somatic embryos on medium containing NPA leads to the formation of embryos with poor meristem formation and fused cotyledons, and to a pin-formed phenotype of the regenerated plantlets similar to what is commonly seen on angiosperm embryos. 15,25,26 Consequently, PAT seems to, like in angiosperms, play a crucial role in apical-basal axis formation in Picea abies.…”
Section: Discussionmentioning
confidence: 73%
“…A recent study by us, 2 along with a study by Larsson et al 24 have shown that growth of somatic embryos on medium containing NPA leads to the formation of embryos with poor meristem formation and fused cotyledons, and to a pin-formed phenotype of the regenerated plantlets similar to what is commonly seen on angiosperm embryos. 15,25,26 Consequently, PAT seems to, like in angiosperms, play a crucial role in apical-basal axis formation in Picea abies.…”
Section: Discussionmentioning
confidence: 73%
“…The expression of the auxin efflux transporter PIN1 had been observed in differentiating procambium, running from the tips of cotyledons down throughout the somatic embryo axis and to the root apical meristem of Picea abies [38]. The centrality of polar auxin transport for the correct patterning of both apical and basal parts of spruce embryos throughout the whole developmental process has been demonstrated by Larsson et al [39] using naphthylphthalamic acid (NPA) treatments. The establishment of an auxin transport system is a prerequisite for patterning events in the apical region of embryos at the beginning of the transition from the globular to the heart stage.…”
Section: Discussionmentioning
confidence: 97%
“…Molecular data suggest that angiosperms and gymnosperms shared a final common ancestor about 300 million years ago (Smith et al 2010) and later evolved different embryo development pathways. Despite the different patterning during embryo development, significant homologies between conifers and angiosperms have been shown, for example, in apical-basal embryo patterning driven by polar auxin transport (Larsson et al 2008a(Larsson et al , b, 2012a and in radial patterning (Zhu et al 2016). In addition, out of 295…”
Section: Communicated By P Ingvarssonmentioning
confidence: 99%
“…The developmental stages of Scots pine and Norway spruce somatic embryogenesis have been described before in Abrahamsson et al (2012) and Larsson et al (2008a), respectively, and are schematically compared in Table S4. Embryogenic cultures of both species proliferate as different types of cell aggregates composed of small rounded cells with dense cytoplasm in combination with elongated cells harboring large vacuoles.…”
Section: Zygotic and Somatic Embryo Development In Scots Pine And Normentioning
confidence: 99%